Uncoupling Effect of F16 Is Responsible for Its Mitochondrial Toxicity and Anticancer Activity. (23rd October 2017) - Wang, Jia; He, Huan; Xiang, Chen; Fan, Xiao-Yang; Yang, Li-Yun; Yuan, Lian; Jiang, Feng-Lei; Liu, Yi
Abstract: As a novel delocalized lipophilic cation, F16 selectively accumulates in mitochondria of carcinoma cells and shows a broad spectrum of antiproliferative action towards cancer cell lines. In order to reveal the mode of action and molecular mechanism of F16 inducing cytotoxicity, we investigated the effects of F16 on cancer cells and isolated mitochondria relative to its precursor compound ( E )-3-(2-(pyridine-4yl)vinyl)-1 H -indole (PVI), which has a similar structure without positive charge. It was found that PVI did not accumulate in mitochondria, and exhibited lower cytotoxicity compared to F16. However, when they were directly incubated with mitochondria, both F16 and PVI were observed to induce damage to mitochondrial structure and function. Moreover, it was found that F16 as well as PVI acted as uncouplers on mitochondria, and further rescue experiments revealed that the addition of adenosine 5′-triphosphate was the most effective way to recover the cell viability decreased by F16. Thus it was concluded that the decreased intracellular adenosine 5′-triphosphate availability induced by the uncoupling effect of F16 was a major factor in F16-mediated cytotoxicity. Futhermore, the results indicated that the uncoupling effect of F16 is attributed to its chemical stucture in common with PVI but independent of its positive charge. The study may shed light on understanding the underlying mechanism of action for F16, and providing suggestions for the design of new mitochondria-targeted antitumor molecules.